(untitled) (Indian Journal of Child Health, 2020)
Background: It is important to understand the role of various feeding practices during infancy on the development of the cardiac structures, to intervene early with the prevention of cardiovascular disease. Aim: The aim of the study was to compare the structures and functions of the right side of the heart in exclusively breastfed (EBF) and formula-fed (FF) babies in the 1st year of life. Methods: A cross-sectional study was conducted for 76 healthy infants aged 3–24 months of life of whom 38 were EBF and 38 were FF in the first 6 months of life. The right ventricular functions and dimensions of the chamber were assessed by echocardiography. The measurements included percent fractional shortening (%FS), right ventricular velocity time integral (RV-VTI), cardiac output, and tricuspid annular plane systolic excursion (TAPSE), e prime, and s prime. Results: Mean values of %FS for the right side were significantly higher in EBF infants in 51.33±5.20 than in FF infants (49.22±3.75) at p<0.05. There was a significant increase in mean RV VTI values in EBF infants (17.2±2.73) than FF infants (15.9±1.94) p<0.01. We noticed a significant increase (Cardiac Output) in EBF infants (5.81±1.01) than FF infants (5.26±1.18). TAPSE was significantly higher in EBF infants (1.56±0.18) than FF infants (1.46 ±0.20) at p<0.05. Conclusion: EBF in infancy supports the higher performance of the right side of the heart in infancy.